Trauma and Character Transformation in Charles Dickens' A Christmas Carol - Youvelka Shahia Ridha; Ruly Indra Darmawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the emotional trauma and psychological transformation of Ebenezer Scrooge in Charles Dickens’ A Christmas Carol through Jacques Lacan’s psychoanalytic framework, focusing on the Imaginary, Symbolic, and Real orders. The study aims to identify the experiences underlying Scrooge’s trauma and to analyze how his encounters with the three ghosts facilitate his process of self-healing and transformation. Employing a qualitative descriptive method, this research uses close reading and textual analysis of selected excerpts from the novel. The findings reveal that Scrooge’s trauma stems from cumulative experiences of emotional neglect, loss, and isolation, which disrupt his identity formation and result in emotional detachment, distorted values, and social alienation. These conditions are reflected across Lacan’s three orders: fragmented self-perception in the Imaginary, disconnection from social structures in the Symbolic, and unresolved emotional conflict in the Real. Furthermore, the encounters with the Ghosts of Christmas Past, Present, and Yet to function as a structured psychological process that enables Scrooge to confront, reinterpret, and integrate his traumatic experiences. This process leads to increased self-awareness, emotional growth, and identity reconstruction, ultimately transforming him into a more compassionate individual. The study highlights that trauma not only shapes identity but can also be restructured through confrontation and symbolic reintegration, demonstrating the relevance of Lacanian theory in literary analysis.